Relationship between the socioeconomic, sociodemographic and BTL publicity factors in the incidence of childhood obesity in Cuenca-Ecuador - Ríos Ponce, Marco Antonio (2019)
Fil: Ríos Ponce, Marco Antonio. University of Azuay. Faculty of Administration Sciences; Ecuador.